1998
DOI: 10.1021/bp970133x
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Transfer Properties of Microbubbles. 1. Experimental Studies

Abstract: Synthesis-gas fermentations have typically been gas-to-liquid mass-transfer-limited due to low solubilities of the gaseous substrates. A potential method to enhance mass-transfer rates is to sparge with microbubble dispersions. Mass-transfer coefficients for microbubble dispersions were measured in a bubble column. Oxygen microbubbles were formed in a dilute Tween 20 solution using a spinning disk apparatus. Axial dispersion coefficients measured for the bubble column ranged from 1.5 to 7.2 cm2/s and were esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 25 publications
2
112
0
1
Order By: Relevance
“…Weber (2003) used microbubble dispersion to cultivate Trichoderma reesei for cellulose enzyme production. In an anaerobic fermentation, Bredwell and Worden (1998) applied the MBD to increase the mass transfer of synthesis gas to produce ethanol and butanol.…”
Section: Microbubble Dispersion In Fermentationmentioning
confidence: 99%
“…Weber (2003) used microbubble dispersion to cultivate Trichoderma reesei for cellulose enzyme production. In an anaerobic fermentation, Bredwell and Worden (1998) applied the MBD to increase the mass transfer of synthesis gas to produce ethanol and butanol.…”
Section: Microbubble Dispersion In Fermentationmentioning
confidence: 99%
“…Klasson et al (1990a) used two STRs in series and reported a 30 fold increase in ethanol productivity using C. ljungdahlii. Bredwell and Worden (1998) showed that the use of a microsparger in a STR for production of acetate, ethanol and butyrate by Butyribacterium methylotrophicum increased the mass transfer by six times with 50% of the flow rate used without a microsparger. The highest ethanol concentration of 48 g/L was produced in a continuous syngas fermentation in a CSTR with cell recycle (Phillips et al, 1993).…”
Section: Bioreactor Designmentioning
confidence: 99%
“…Mass transfer characteristics of various reactor configurations have compared by many researchers (Bredwell and Worden, 1998;Cowger et al, 1992;Jones, 2007;Klasson et al, 1990b;Klasson et al, 1991;Klasson et al, 1993a;Munasinghe and Khanal, 2010b;Munasinghe and Khanal, 2014;Orgill et al, 2013;Riggs and Heindel, 2006;Shen et al, 2014a;Yasin et al, 2014). In a STR, the mass transfer coefficient can be increased by increasing 268-280.…”
Section: Bioreactor Designmentioning
confidence: 99%
“…Most applications of colloidal gas aphrons take advantage of (i) their large interfacial area, (ii) the adsorption of particles at the microbubble interfaces, and (iii) their stability for enhanced mass transfer [3]. Possible applications include (1) separation, (2) oil recovery, (3) firefighting, (4) fermentation and bioreactors, (5) material synthesis, and wherever macroscopic foams are currently being used.…”
Section: Motivationsmentioning
confidence: 99%
“…They studied the liquid drainage rate in CGA dispersion and the bubble rise velocity. Bredwell and Worden [3] estimated the shell thickness to be 200-300 nm for nonionic surfactant Tween-20, based on the study of gas diffusion from the CGA bubble to the liquid bulk, assuming that the mass transfer is limited by the rate of diffusion across the shell. More recently, Jauregi et al [26] employed freeze fracture with TEM and X-ray diffraction to study the structure of the soapy shell.…”
Section: Cga Structurementioning
confidence: 99%